Non-canonical DNA/RNA structures associated with the pathogenesis of Fragile X-associated tremor/ataxia syndrome and Fragile X syndrome - Yousuf, Aadil; Ahmed, Nadeem; Qurashi, Abrar (Frontiers in Genetics, 2022)
Fragile X-associated tremor/ataxia syndrome (FXTAS) and fragile X syndrome (FXS) are primary examples of fragile X-related disorders (FXDs) caused by abnormal expansion of CGG repeats above a certain threshold in the 5′-untranslated region of the fragile X mental retardation (FMR1) gene. Both diseases have distinct clinical manifestations and molecular pathogenesis. FXTAS is a late-adult-onset neurodegenerative disorder caused by a premutation (PM) allele (CGG expansion of 55–200 repeats)), resulting in FMR1 gene hyperexpression. On the other hand, FXS is a neurodevelopmental disorder that results from a full mutation (FM) allele (CGG expansions of ≥200 repeats) leading to heterochromatization and transcriptional silencing of the FMR1 gene. The main challenge is to determine how CGG repeat expansion affects the fundamentally distinct nature of FMR1 expression in FM and PM ranges. Abnormal CGG repeat expansions form a variety of non-canonical DNA and RNA structures that can disrupt various cellular processes and cause distinct effects in PM and FM alleles. Here, we review these structures and how they are related to underlying mutations and disease pathology in FXS and FXTAS. Finally, as new CGG expansions within the genome have been identified, it will be interesting to determine their implications in disease pathology and treatment.